(3JdNjU TQM aUhd CHbQGWs - (3TQa GdOjf Ydj Hf jhSa Hf MjOQI Hf GdMSf GdQMjHis; (3YHO GdQMef Hf Ydj Hf CMeO Hf CHj UGOb, CHh GdbGSe GdfjSGHhQqj,J (B470 (3g` ? s ((3MSf Hf YjSi GdCfbQdi GdMfai s)
(3ChdgG (B:s
(3CeG HYO (B: (3aEf cJGH GdaUhd dhGdO GdCWHGA CHbQGW CaVd GdcJH GdWjHI GdcJH GdWHjI s
(3BNQgG (B:s
(3hCeG GdaUhd GdeOdSI hGdecQQI aJQcfG PcQgG , TabI Ydi ahJ GdReGf ajeG dG jLO faYkG hGddg hdi GdNjQ , hgh MSHfG hfYe Gdhcjd s
(3ChaQ GdTQhMs
(3TQM ajg Hf CHj GdUGOb aUhd CHbQGWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdWHs